The Conformation of the Intrinsically Disordered N-Terminal Region of Barrier-to-Autointegration Factor (BAF) is Regulated by pH and Phosphorylation. Issue 2 (30th January 2023) - Marcelot, Agathe; Zinn-Justin, Sophie; Cuniasse, Philippe
Graphical abstract: Highlights: MD simulations show the particular conformational flexibility of BAF N-ter. S4/T3 di-phosphorylation is required to reduce the dispersion of BAF conformations. MD simulations and NMR pH titration highlight the influence of H7 protonation. Di-phosphorylation leads the structure of BAF closer to that observed in the crystal. MD supported by NMR unveils the interactions for pBAF conformational restriction. Abstract: Barrier-to-Autointegration Factor (BAF) is a highly conserved DNA binding protein important for genome integrity. Its localization and function are regulated through phosphorylation. Previously reported structures of BAF suggested that it is fully ordered, but our recent NMR analysis revealed that its N-terminal region is flexible in solution and that S4/T3 di-phosphorylation by VRK1 reduces this flexibility. Here, molecular dynamics (MD) simulation was used to unveil the conformational ensembles accessible to the N-terminal region of BAF either unphosphorylated, mono-phosphorylated on S4 or di-phosphorylated on S4/T3 (pBAF) and to reveal the interactions that contribute to define these ensembles. We show that the intrinsic flexibility observed in the N-terminal region of BAF is reduced by S4 phosphorylation and to a larger extent by S4/T3 di-phosphorylation. Thanks to the atomic description offered by MD supported by the NMR study of several BAF mutants, we identified the dynamic network of salt bridge interactions responsible for the conformational restriction involving pS4 and pT3 with residues located in helix α1 and α6. Using MD, we showed that the flexibility in the N-terminal region of BAF depends on the ionic strength and on the pH. We show that the presence of two negative charges of the phosphoryl groups is required for a substantial decrease in flexibility in pBAF. Using MD supported by NMR, we also showed that H7 deprotonation reduces the flexibility in the N-terminal region of BAF. Thus, the conformation of the intrinsically disordered N-terminal region of BAF is highly tunable, likely related to its diverse functions.